An IoT Based Home Security System With ESP32, Video Monitoring, and Blynk Integration - Azlan, Muhammad Uthman; Mohd Shamian Zainal, (Progress in Engineering Application and Technology, 2024)
IoT-based home security systems have grown in popularity as an innovative and comprehensive option for protecting residential properties. These systems make use of networked devices including motion sensors, surveillance cameras, and a centralised control hub, which are all linked via the Internet of Things (IoT). This paper describes an Internet of Things (IoT)-based home security system with ESP32, video monitoring and Blynk integration. This project stands out from others in the realm of home security systems by leveraging components, such as the ESP32-CAM module, which are not commonly employed in conventional designs. The utilization of these distinctive components sets this project apart, offering a unique and innovative approach to home security that diverges from mainstream solutions.